Coverage of maternal health services to maternal mortality ratio moderated by public health center accreditation status and causes of maternal death - Eka Nur Sejati; Elsye Maria Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Maternal mortality is a benchmark in monitoring maternal health globally, the quality of reproductive health services in general, and the country's development towards the Sustainable Development Goals. The purpose of this study was to determine the effect of maternal health service coverage on the Maternal Mortality Ratio (MMR) moderated by the accreditation status of public health centers (PHC) and the causes of maternal mortality. This research is a quantitative analytic method of observational cross-sectional design. The research subjects included all pregnant women, mothers in labor, and postpartum mothers in Indonesia in 2020 with a total sampling technique. The data on the results of health program achievements in Indonesia in 2020, conducted a path analysis using the SmartPLS program. The coverage of maternal health services had a significant negative effect of 54.9% on the MMR (p=0.036) and a significant positive effect of 59.2% on the accreditation status of PHC (p=0.002). The accreditation status of PHC and causes of maternal death did not significantly affect the MMR (p=0.632; p=0.531). The coverage of maternal health services mediated by the accreditation status of PHC did not significantly affect the MMR (p=0.657). The coverage of maternal health services moderated by the accreditation status of PHC and causes of maternal death did not significantly affect the MMR (p=0.643; p=0.318). Increasing the coverage of maternal health services can reduce the MMR and improve the accreditation of PHC. The results of this study can be used as material for evaluation and motivation to increase the coverage of maternal health services in PHC.Abstrak: Kematian ibu merupakan tolak ukur dalam memonitor kesehatan ibu secara global, kualitas pelayanan kesehatan reproduksi secara umum, dan perkembangan negara dalam Sustainable Development Goals (SDGs). Tujuan penelitian ini adalah untuk mengetahui pengaruh cakupan pelayanan kesehatan maternal terhadap rasio kematian ibu dimoderasi oleh status akreditasi Puskesmas dan penyebab kematian ibu. Penelitian ini merupakan kuantitatif metode analitik observasional desain cross sectional. Subjek penelitian meliputi seluruh ibu hamil, ibu bersalin, dan ibu nifas di Indonesia pada tahun 2020 dengan teknik total sampling. Data hasil capaian program kesehatan di Indonesia pada tahun 2020 dilakukan analisis jalur menggunakan program SmartPLS. Cakupan pelayanan kesehatan maternal berpengaruh negatif signifikan 54,9% terhadap rasio kematian ibu (p=0,036) dan berpengaruh positif signifikan 59,2% terhadap status akreditasi Puskesmas (p=0,002). Status akreditasi Puskesmas dan penyebab kematian ibu tidak berpengaruh signifikan terhadap rasio kematian ibu (p=0,632; p=0,531). Cakupan pelayanan kesehatan maternal yang dimediasi oleh status akreditasi Puskesmas tidak berpengaruh signifikan terhadap rasio kematian ibu (p=0,657). Cakupan pelayanan kesehatan maternal yang dimoderasi oleh status akreditasi Puskesmas dan penyebab kematian ibu tidak berpengaruh signifikan terhadap rasio kematian ibu (p=0,643; p=0,318). Peningkatan cakupan pelayanan kesehatan maternal dapat menurunkan rasio kematian ibu dan meningkatkan status akreditasi Puskesmas. Hasil penelitian ini dapat dijadikan sebagai bahan evaluasi dan motivasi untuk meningkatkan cakupan pelayanan kesehatan maternal di Puskesmas.